e-Assessment Cloud Solution: Architecture, Organization and Cost Model - Gusev, Marjan; Ristov, Sasko; Arminski, Goce; Velkoski, Goran; Bozinoski, Krste (International Journal of Emerging Technologies in Learning (iJET), 2013)
Several challenges address the existing e-Assessment systems, such as accurate evaluation, security and data privacy, performance, scalability etc. Our focus in this paper is on e-Assessment scalability and performance. We have developed a new SOA architecture of a cloud hosted e-Assessment system to achieve sustainable performance as a highly scalable and elastic solution. The proposed organization solution is based on three modules (subsystems): management module, reporting module, and assessment module. The built in logic enables an efficient environment where minimum resources will be utilized during exploitation. The proposed system organization ensures that the assessment module, as active subsystem for each assessment, will work with much smaller data compared to the centralized one. The cost model developed for this solution analysis this cloud based solution against the existing e-Assessment web application.Therefore, we expect that this solution will have several benefits, like overall cost reduction and better performance.